Overlay GHC: An Extension of Guarded Horn Clauses for Overlay Programming - Saito, K. (2008 19th International Workshop on Database and Expert Systems Applications, 2008)
Today's high-speed network allows sophisticated applications of overlay networks. Meanwhile, usage of multicore processors has been spreading. The level of concurrency we need to handle has been rising rapidly, which necessitates a language that can express massive concurrency in a natural way, which can work with both tightly and loosely-coupled multiprocessor environments. This paper describes still work-in-progress design of "overlay GHC", an overlay network programming language based on concurrent logic language GHC (guarded Horn clauses), as a candidate for such a language.